Linguistic Crisis Prediction: An Integration of the Linguistic Category Model in Crisis Communication. (October 2019) - Borden, Jonathan; Zhang, Xiaochen Angela
Through two experiments, this study examines the relationship between linguistic choice and attribution perception in organizational crisis. Experiment 1 demonstrated that abstract (vs. concrete) language in crisis news elicited higher attribution and lower purchase intentions. Experiment two showed that preventable (vs. victim) crisis led to higher usage of abstract language in describing and commenting on the crisis. Also, abstract language use in describing and commenting on the crisis mediates crisis clusters' effect on purchase intentions. Furthermore, attribution of crisis responsibility mediated crisis cluster and in-group/out-group's effects on abstract language use in describing and commenting on the crisis. The findings empirically connect two attribution theory-rooted theories: linguistic category model and the situational crisis communication theory.